Use of a Low-Molecular Weight Heparin (Enoxaparin) or of a Phenformin-like Substance (Moroxydine Chloride) in Primary Early Recurrent Aborters with an Impaired Fibrinolytic Capacity - Gris, Jean-Christophe; Neveu, Sylvie; Tailland, Marie-Laure; Courtieu, Christophe; Marès, Pierre; Schved, Jean-François (Thrombosis and Haemostasis, 1995)
An impaired fibrinolytic capacity, defined as an insufficient venous occlusion-induced shortening of the plasma euglobulin clot lysis time, is a common feature in women suffering from primary early recurrent unexplained miscarriages (1,2). We investigated the therapeutic effect of a low-molecular-weight heparin and of a phenformin-like substance.In a prospective, randomized trial, 30 consecutive patients initially received either enoxaparin, 20 mg per day during one month, or moroxydine chloride, 1200 mg per day during one month. In case of fibrinolytic status normalization, they were treated during 6 months by the beneficial treatment which was planned to be continued during eventual pregnancies. Patients with hypofibrinolysis persistence received the alternative treatment during another month and a new evaluation was performed. No treatment was given when a persistent abnormal response to the venous occlusion test was evidenced. In case of positive response, the treatment was continued during 6 months. The primary study end-points consisted of any of the following: effect of the treatments on the fibrinolytic response; number of patients becoming pregnant during the 6 months following the last venous occlusion test; number of full-term pregnancies.Concerning the effects on the fibrinolytic system, 20 out of 29 women responded to the first or second-line enoxaparin treatment whereas only 1 woman out of 19 responded to moroxydine chloride (p=0.00002). Concerning the effects on fertility, responders to LMWH were more likely to initiate a new pregnancy than non-responders (16/20 vs 2/10, p=0.002). In patients conceiving, LMWH responders were more likely to obtain live births than nonresponders (13/16 vs. 0/2, p=0.02). The 9 women who had not responded to both treatments and the one who had responded to moroxydine chloride are still childless. Thirteen of the 20 previously childless women who had responded to enoxaparin had a successful pregnancy whilst taking the low-molecular weight heparin (p=0.0009).The low-molecular weight heparin enoxaparin was associated with successful pregnancies in patients with recurrent unexplained miscarriages associated with an impaired fibrinolytic capacity.